DETERMINANTS OF SABAH TAMU BUSINESS OPERATOR'S MOTIVATION TO REMAIN IN THE TAMU BUSINESS - Jaratin Lily; Sidah Idris; Zuraidah Jamrin; Al Nasrie Weli, (Malaysian Journal of Business and Economics (MJBE), 2024)
The Tamu, the traditional market known in Sabah, is a platform for entrepreneurial activity. This study aims to determine factors influencing Sabah Tamu business operator's motivation to remain in the Tamu business. The self-administered questionnaires were distributed through in-person survey and online survey. There were 125 questionnaires successfully gathered for data analysis. The findings showed that entrepreneurs' attitude, skill and resources positively affect the Tamu business operator's motivation to remain in the Tamu business. However, socio-cultural has no significant relationship with the motivation to remain of Sabah Tamu operators. The study results provide insight into the Tamu business operator's motivation to remain in the Tamu business, which government agencies may consider mitigating the adverse financial impact faced by the operator of the Tamu through relevant regulations and support programmes.